2019
DOI: 10.3389/fphar.2019.00167
|View full text |Cite
|
Sign up to set email alerts
|

Can Positive Framing Reduce Nocebo Side Effects? Current Evidence and Recommendation for Future Research

Abstract: Although critical for informed consent, side effect warnings can contribute directly to poorer patient outcomes because they often induce negative expectations that trigger nocebo side effects. Communication strategies that reduce the development of nocebo side effects whilst maintaining informed consent are therefore of considerable interest. We reviewed theoretical and empirical evidence for the use of framing strategies to achieve this. Framing refers to the way in which information about the likelihood or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 59 publications
3
72
1
2
Order By: Relevance
“…Those who received the positively framed PIL reported fewer side-effects (n=40 vs n=55). Other studies have reported similar findings 46. Full disclosure about the risks is conveyed in both types of frames.…”
Section: Reducing Unnecessary Nocebo Effectssupporting
confidence: 72%
“…Those who received the positively framed PIL reported fewer side-effects (n=40 vs n=55). Other studies have reported similar findings 46. Full disclosure about the risks is conveyed in both types of frames.…”
Section: Reducing Unnecessary Nocebo Effectssupporting
confidence: 72%
“…Nocebo-Effekte können z. T. auch durch den gewählten Bezugsrahmen ("Framing") verringert werden, indem die Risikowahrscheinlichkeit positiv formuliert wird: "90 % der Patienten vertragen das Medikament gut" statt "Bei 10 % tritt eine Nebenwirkung auf " [2]. Dabei sollten Negationen ("Bei 90 % tritt diese Nebenwirkung nicht auf ", "Die meisten Patienten haben keine Schmerzen") vermieden werden, weil sich starke negative Suggestionen nicht mit einem "nicht" auslöschen lassen [11].…”
Section: Positive Formulierungunclassified
“…These two types of control conditions are not exhaustive. For example, as indicated in Table 1 , other variations could include giving participants a treatment with “standard” or usual care information in order to test the effect of other information provision strategies, for example, standard information versus positive framing of information about adverse outcomes, which focuses on the proportion of patients who will not experience these unpleasant outcomes (16, 17). Of most importance, however, is that researchers consider carefully their hypotheses and relevance to clinical practice, consider which factor(s) differ between their chosen conditions, and utilize appropriate control conditions in experimental designs that will allow them to most appropriately test their research question.…”
Section: Nocebo Effects and Nocebo Side Effects: Control Conditionsmentioning
confidence: 99%